Pharmacokinetics of Cannabidiol Following Intranasal, Intrarectal, and Oral Administration in Healthy Dogs - Polidoro, Dakir; Temmerman, Robin; Devreese, Mathias; Charalambous, Marios; Ham, Luc Van; Cornelis, Ine; Broeckx, Bart J. G.; Mandigers, Paul J. J.; Fischer, Andrea; Storch, Jan; Bhatti, Sofie F. M. (Frontiers in Veterinary Science, 2022)
The therapeutic potential of cannabidiol (CBD), a non-psychtropic component of the Cannabis sativa plant, is substantiated more and more. We aimed to determine the pharmacokinetic behavior of CBD after a single dose via intranasal (IN) and intrarectal (IR) administration in six healthy dogs and compare to the oral administration route (PO). Each dog underwent the same protocol but received CBD through a different administration route. CBD plasma concentrations were determined by ultra-high performance liquid chromatography-tandem mass spectrometry before and at fixed time points after administration. Non-compartmental analysis was performed on the plasma concentration-time profiles. Plasma CBD concentrations after IR administration were below the limit of quantification. Following standardized dosages applied IN (20mg) or PO (100 mg), the mean area under the curve (AUC) after IN and PO CBD administration was 61 and 1376 ng/mL*h, respectively. The maximal plasma CBD concentration (Cmax) after IN and PO CBD administration was 28 and 217 ng/mL reached after 0.5 and 3.5h (Tmax), respectively. Significant differences between IN and PO administration were found in the Tmax (p = 0.04). Higher AUC and Cmax were achieved with 100 mg PO compared to 20 mg IN, but no significant differences were found when AUC (p = 0.09) and Cmax (p = 0.44) were normalized to 1 mg dosages. IN administration of CBD resulted in faster absorption when compared to PO administration. However, PO remains the most favorable route for CBD delivery due to its more feasible administration. The IR administration route is not advised for clinical application.